Diagnosis of Heart Disease Using Feature Selection Methods Based On Recurrent Fuzzy Neural Networks - Shirin Kordnoori; Hamidreza Mostafaei; Mohsen Rostamy-Malkhalifeh; Mohammadmohsen Ostadrahimi; Saeed Agha Banihashemi (IPTEK The Journal for Technology and Science, 2021)
The World Health Organization (WHO) estimated one-third of all global deaths reason by cardiovascular diseases. Nowadays, artificial intelligence attracts many considerations in diagnosing heart disease. This study used trained recurrent fuzzy neural networks (RFNN) for diagnosing heart disease. This study also used five kinds of feature selection and extraction models for comparing the action of a model, such as data envelopment analysis (DEA), Linear Discriminative Analysis (LDA), Principle Component Analysis (PCA), Correlation Feature Selection (CFS), and Relief. By using these methods, this paper diagnosed whether the patient has a heart disease problem or not. The results showed that Correlation feature selection has the best operation in feature selection in RFNN by accuracy of 98.4%.